From Watching to Speaking? Indonesian EFL Students’ Engagement with English Role-play Content on Instagram Reels - Indawan Syahri; Asti Gumartifa; Amanah Nurussakinah (VELES Voices of English Language Education Society, 2026)
Speaking remains a persistent challenge for Indonesian EFL learners, partly because classroom instruction often provides limited opportunities for meaningful oral practice. At the same time, students’ frequent engagement with short-form social media videos, particularly Instagram Reels, offers potential exposure to authentic, contextualized spoken English. This study investigated students’ engagement with English roleplay content on Instagram Reels and its perceived contribution to EFL speaking learning. Using a qualitative descriptive design, data were collected from 32 eleventh-grade students in a bilingual class at a public senior high school through closed-ended and open-ended questionnaires. The data were analyzed using descriptive statistics and thematic analysis to identify patterns in emotional, cognitive, and behavioral engagement, as well as perceived speaking-related benefits and challenges. The findings revealed that students demonstrated strong emotional engagement, reflected in enjoyment, interest, and reduced learning pressure, and high cognitive engagement, shown through efforts to understand, remember, and notice vocabulary, pronunciation, expressions, and contextual language use. Behavioral engagement was mainly reflected in frequent viewing and imitation, while direct interaction and original content creation remained limited due to low confidence and fear of public judgment. Students perceived English roleplay Reels as helpful for improving pronunciation, vocabulary exposure, fluency awareness, tone, expression, and comfort in speaking English. However, distraction from entertainment content, time management issues, technical constraints, and limited confidence in producing videos constrained its pedagogical value. These findings suggest that Instagram Reels can serve as a supplementary speaking resource when integrated with guided imitation, structured speaking tasks, feedback, and confidence-building activities.